Perancangan dan Pembuatan Website E-Commerce untuk UMKM yang dibina oleh Universitas Kristen Petra - Billy Christi Hartanto; Henry Novianus Palit (Jurnal Infra, 2017)
One of the LPPM program to help people in Rungkut Surabaya city is to guide several UMKM. To increase the quality of service and the profit of UMKM, LPPM created a platform in hope to help promote UMKM products.As the solution is an E-Commerce Website that can fulfill that needs. E-Commerce website in this thesis has several feature. Showing UMKM products, receiveing order, processing order, and checking order status. There is also rating and review feature for giving trust to customer that want to buy products from UMKM. System also has SMS Gateway feature to make UMKM easier to process order without accesing the website.As the result from this thesis is an user friendly and supporting online transaction website, this was based on questionare result from customer, UMKM and Administrator. Feature-feature that are built is tested and working as expected. Website is a responsive website so it can be opened with several browser dan handphone with different screen resolution.